More Tales from Shakespeare - William Shakespeare; Geoffrey Whittam; G. Horsley; Charles Lamb; Mary Lamb (UK Longman, 1989)
The Book Contains the Following Tales: The Winter's Tale King Lear the Taming of The Shrew Romeo and Juliet Hamlet, Prince of Denmark Othello . Questions
2000 Word Vocabulary
Keywords: Literature (3GdCOHs; General